Synergistic effect of farmyard manure on soil organic carbon and carbon sequesration potential in fodder cowpea (Vigna unguiculata) in different agroclimatic zones - B. Rajesh Kumar; Thanga Tamil Vanan; T. Sivakumar``; K.N. Selvakumar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The experiment was conducted to study the influence of inorganic fertilizer (Treatment 1) and its synergistic effect with organic fertilizer (Treatment 2) on soil organic carbon (SOC) and carbon sequestration potential (CSP) in Fodder Cowpea (Vigna unguiculata) crop field in North Eastern and Western Zones of Tamil Nadu, India during summer season of 2012. In Western zone two districts viz., Coimbatore and Erode districts and in North Eastern Zone Tiruvannamalai and Vellore districts were selected for the field experiments. From each district, two villages were randomly selected for field experiments totaling to eight experimental sites for the study. Fodder cowpea was planted as per standard agronomic practices with soil samples collected on 0, 30 and 60th day (harvest) of the trial. Soil samples were dried and subjected to analysis using Analytikjena multi N/C2100S carbon analyzer. The SOC on 30th day of the experimental period varied from 0.25% to 0.37% for treatment 1 (T1) and 0.27% to 0.41% for treatment 2 (T2) in the experimental zones. The SOC on 60th day varied from 0.29% to 0.42% for T1 and 0.32% to 0.46% for T2. Carbon sequestration potential in the soil for the fodder cowpea crop varied from 0.62 to 0.99 t/ha on 60th day of the trial period. The results indicated that synergistic use of farm yard manure could be a viable option to sequester carbon than inorganic fertilizer alone which has a definite impact on carbon mitigation.